Risk Factors of Coronary Heart Disease in North Sulawesi Indonesia - Ottay, Ronald Immanuel; Nelwan, Jeini Ester; Sumampouwa, Oksfriani Jufri; Ticoalu, Jansje Vera (International Journal of Natural and Health Sciences, 2024)
Coronary heart disease (CHD) is caused by multifactorial such as age, gender, blood pressure, blood sugar, and lipid profiles. This study aims to analyze the description of risk factors for CHD at the North Sulawesi, Indonesia. This is a descriptive research conducted at the Cardio Vascular and Brain Center Cardiology Polyclinic, General Hospital Prof. Dr. R. D. Kandou Manado in December 2021 to January 2022. The respondents of this study were CHD patients, totaling 100 people. The variables in this study were age, gender, blood pressure, blood sugar, and lipid profiles. The data was obtained from the patient's medical record data. Data analysis performed univariately. The results showed that the respondents are most distributed in the age group ≥40 years as many as 99 people (99%), and male sex as many as 73 people (73%). Respondents who do not suffer from hypertension are 56 people (56%) more than those who suffer from hypertension, namely 44 people (44%). Respondents with GDP >126 mg/dL were 57 people (57%) more than those with GDP < the same as 126 mg/dL, namely 43 people (43%). Respondents whose total cholesterol level was < equal to 240 mg/dL were more than 60 people (60%) compared to patients with cholesterol levels > 240 mg/dL which were 40 people (40%). It can be concluded that the risk factors for CHD at the North Sulawesi, Indonesia was ≥40 years old, male, more patients with blood pressure <140/90 mmHg, more patients with GDP >126 mg/dL and more patient with total cholesterol level <240 mg/dL